Professionalism and Occupational Well-Being: Similarities and Differences Among Latin American Health Professionals - San-Martín, Montserrat; Delgado-Bolton, Roberto; Vivanco, Luis (Frontiers in Psychology, 2017)
Context: Empathy, teamwork, and lifelong learning are described as key elements of professionalism. The first recipients of their benefits are professionals themselves. Paradoxically, scarce studies have reported association between professionalism and occupational well-being. The main purpose of this study was to characterize the influence that empathy, teamwork, and lifelong learning, play in the occupational well-being of physicians and nurses working in Latin American healthcare institutions. Methods: The Jefferson Scale of Empathy, the Jefferson Scale of Attitudes toward Physician-Nurse Collaboration, the Jefferson Scale of Physicians Lifelong Learning, and the Scale of Collateral Effects (somatization, exhaustion, and work alienation), were administered to 522 physicians and nurses working in institutions of Mexico, Colombia, Ecuador, and Argentina. Internal reliability was calculated. Gender and discipline were used as explanatory variables in comparison analysis. Two-way analysis of variance was performed to examine differences due to the main effects of the gender, and discipline, and to determine possible combined effects. Correlation analysis was performed to measure associations between collateral effects and age, and between collateral effects and professionalism. Results: A total of 353 (68%) surveys were returned fully completed. Adequate reliability was confirmed in all instruments. No differences were found among countries for collateral effects. Correlation analysis confirmed in physicians an inverse association between empathy and collateral effects (P=–0.16; p<0.05), and between collateral effects and lifelong learning (P=–0.18; p<0.01). In nurses, this association was confirmed only for empathy (P=–0.19; p<0.05). Important differences in the development of professionalism and in its effects on occupational well-being appeared associated to inter-professional collaboration and work roles. An inverse correlation between age and collateral effects was confirmed in physicians (P=–0.22; p<0.001) and in nurses (P=–28; p<0.001). Comparison by gender confirmed higher somatization in women physicians and nurses than in men groups (p<0.001). On the other hand, comparison by discipline confirmed higher exhaustion and alienation in physicians than in nurses (p<0.01). Conclusions: The findings support the importance that empathy, teamwork, and lifelong learning have in practitioners’ health and welfare, and the role that cultural behaviors, associated to work professional models and social stereotypes, play in the interaction between professionalism and occupational well-being.